A Case of Septicemia due to Nonocclusive Mesenteric Ischemia Occurring in Induction Chemotherapy - Hideki Tanaka; Kiyoaki Tsukahara; Isaku Okamoto; Rio Kojima; Kazuhiro Hirasawa; Hiroki Sato (Case Reports in Otolaryngology)
In nonocclusive mesenteric ischemia (NOMI), mesenteric ischemia and intestinal necrosis occur despite the absence of organic blockage in mesenteric blood vessels. As abdominal pain is often absent and few characteristic findings are seen in blood biochemistry, imaging diagnosis or other examinations, discovery is often delayed. With a mortality rate of 56–79%, NOMI is a very serious disease. However, few reports have described this pathology in association with chemotherapy regimens such as those used for malignant head and neck tumors. We encountered a case of NOMI during induction therapy combining cisplatin, docetaxel, and 5-fluorouracil. The patient was a 74-year-old man receiving chemotherapy for T2N2bM0 stage IVA oropharyngeal carcinoma. Febrile neutropenia appeared on treatment day 8. An antibacterial agent and a granulocyte colony-stimulating factor were administered, but septic shock developed and he was transferred to the intensive care unit. Abdominal distension was present and contrast-enhanced computed tomography of the abdomen suggested NOMI. Emergency surgery on day 9 resected the necrotized small intestine and created a single-hole ileostomy. The patient subsequently recovered with 2 weeks of continuous hemodiafiltration and other intensive therapies. Otolaryngological surgeons seldom encounter intestinal diseases, which are thus easily overlooked. The present case report may help in achieving early diagnosis.